The state of access : success and failure of democracies to create equal opportunities - Jong, Jorrit de; Rizvi, Gowher (Innovative governance in the 21st century., 2008)
"A comparative, cross-disciplinary exploration of the ways in which democratic institutions fail or succeed to create the equal opportunities that they have promised to deliver to the people they serve"--Provided by publisher.